2021
DOI: 10.3390/jcm10122679
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for and Frequency of CT Scans, Steroid Use, and Repeat Visits in Inflammatory Bowel Disease Patients Seen at a Single-Center Emergency Department: A Retrospective Cohort Study

Abstract: Patients with inflammatory bowel disease often present to the emergency department due to the chronic relapsing nature of the disease. Previous studies have shown younger patients to have an increased frequency of emergency department visits, resulting in repeated exposure to imaging studies and steroids, both of which are associated with risks. We performed a retrospective cohort analysis of inflammatory bowel disease patients seen at Houston Methodist Hospital’s emergency department from January 2014 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Steroids, which are either derived from dietary sources or synthesized within the body, are defined by their distinctive four-ring carbon structure and play vital roles as hormones in various physiological functions. These compounds have been employed in numerous therapeutic applications for a broad array of human disorders [ 38 , 39 , 40 ], such as vascular conditions, although their use continues to be a subject of debate [ 41 ]. Specifically, the importance of progesterone (PRG), a key female sex steroid, in preserving the integrity of the blood–brain barrier has been the focus of extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Steroids, which are either derived from dietary sources or synthesized within the body, are defined by their distinctive four-ring carbon structure and play vital roles as hormones in various physiological functions. These compounds have been employed in numerous therapeutic applications for a broad array of human disorders [ 38 , 39 , 40 ], such as vascular conditions, although their use continues to be a subject of debate [ 41 ]. Specifically, the importance of progesterone (PRG), a key female sex steroid, in preserving the integrity of the blood–brain barrier has been the focus of extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of IBD is increasing worldwide, including Europe, North America, and some developing countries [ 9 , 10 ]. The prevalence of IBD is equal between men and women [ 11 ]. Several studies have reported that patients with IBD have an increased risk of colorectal cancer [ 12 , 13 ] and extraintestinal malignancies (including cholangiocarcinoma, skin cancer, and hematologic malignancies) [ 14 ], which is believed to be a consequence of immunosuppressive therapies and an underlying inflammatory state [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), is chronic, fluctuating, and relapsing. Due to the complexity of the disease and complications such as strictures, fistulas, or perforations, medical image studies such as computed tomography are usually required to diagnose the disease and manage the complications [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%